If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15(y-4)-2(y-9)+5+(y-6)=0
We multiply parentheses
15y-2y+(y-6)-60+18+5=0
We get rid of parentheses
15y-2y+y-6-60+18+5=0
We add all the numbers together, and all the variables
14y-43=0
We move all terms containing y to the left, all other terms to the right
14y=43
y=43/14
y=3+1/14
| 4/t-2+t/2=-2 | | 8^2-6x-9=0 | | 2z+6=8z-12 | | 8=3z+3 | | 10^2-19x+6=0 | | x+3-4x=24 | | 4y/5-4=3y/4= | | 4y/5-4=3y/4=80 | | k+3(2k-5)=4k-2)-7 | | 3x/2+6=8-x | | -16x+4=-16-20x | | 100-(100*0.05)=x | | 12-y=4 | | 4x^2-9x+12=(x^2+36) | | 4(v-5=8 | | x+2/7=9 | | x/2x-5=99 | | 2z/9-1=-6 | | 47.43=9g+3.96 | | 4y5=0 | | .40c+(.75)(500-c)=340 | | 2x+7/x-7=3x+8/x-2 | | P=1000x1+0.05 | | 3t^2+30t=0 | | (9x+6)/2=3x | | 7-2z=5-z | | 10m+5=13 | | 78(6x-1)=42(10x+5) | | 32(9x-9)=24(6x+6) | | 8(3x-6)=120 | | F(x)=4x2+5x-1 | | 40x^2+172x+112=0 |